Weft Computation of Endek Weaving - Nyoman Dewi Pebryani; Putu Manik Prihatini; Tjok Istri Ratna C.S (International Journal of Applied Sciences and Smart Technologies, 2022)
Endek is a textile produces in Bali with a single ikat technique, specifically weft ikat. Weft ikat means that the pattern is created or drawn on the weft threads before ikat or tying process. The weft threads are transferred into a frame; a frame consists of tens to hundreds of bundles or called traditionally as bulih. Drawing a pattern on a frame requires special expertise as the pattern maker has to translate a two-dimensional pattern into a shape that is distorted on the wide side. Indirectly, this special requirement confines the pattern maker as they have to visualize a distortion shape to be able to draw in the frame. To provide easiness in design exploration, providing various templates and multiplier to automatically distort the template are substantial. Therefore, understanding the manual process on site is important before simulating the formula of weft computation including are templates and multiplier. With this computation, the pattern makers or anyone who has an enthusiast in designing Endek patterns may involve in the design process.